ADEQUATE FUNDING PANACEA FOR ACCREDITATION PROBLEMS IN TERTIARY EDUCATION - Jacob, Ogunode Niyi; Okwudinma, Okonkwo, Cecilia (Journal of Higher Education and Academic Advancement, 2024)
This paper examines the role of adequate funding as a solution to accreditation challenges faced by tertiary institutions in Nigeria. Utilizing secondary data sourced from online and print publications, the study investigates how financial resources impact the accreditation process. The findings reveal that sufficient funding is crucial for the effective implementation of accreditation programs. Specifically, adequate financial support facilitates the preparation for accreditation, aids in the procurement of instructional resources, enables the employment of qualified staff, and ensures the provision of essential infrastructure facilities. The paper underscores that without sufficient funding; tertiary institutions struggle to meet accreditation standards, which in turn affect their educational quality and overall performance. Based on these insights, the paper recommends that the Nigerian government enhance its financial support for tertiary institutions. This increased funding will not only help institutions meet regulatory requirements but also strengthen their capacity to deliver high-quality education, thus contributing to national development and global competitiveness